Influence Of Inflation, Exchange Rate And Number Of Taxable Businesses On The Receipt Of Value Addition Tax (Study At The Regional Office Of DJPB Bengkulu Province) - Susena , Karona Cahya; Hamid, Darwan; Hidayah , Nenden Restu (Utami Publisher, 2025)
Value Added Tax is a tax imposed on the consumption of goods and services within the customs area. The contribution of Value Added Tax is considered important for state income because it is the second largest contributor to this type of tax. Value Added Tax is directly related to people's behavior in consuming goods and services which is closely related to the macroeconomic conditions of a country, therefore this research uses macro-economic variables in the form of inflation and the rupiah exchange rate. Apart from that, internal roles to maximize Value Added Tax revenues also need to be considered, such as the number of Taxable Entrepreneurs who have the obligation to collect, deposit and report Value Added Tax payable. Data on inflation, rupiah exchange rate and number of Taxable Entrepreneurs used are secondary data from 2010-2014. This type of research uses explanatory research using a quantitative approach method. Based on the independent variables in the form of inflation data, the rupiah exchange rate and the number of Taxable Entrepreneurs, while the dependent variable uses Value Added Tax revenues, the analysis technique used is multiple linear regression analysis. Based on the t and F hypothesis tests, the independent variable has a partial and simultaneous influence on the dependent variable. Based on the Adjusted R Square value, it shows that the dependent variable can be explained by 51.3% by the independent variable.